Chemoprofiling as Breeding Tool for Pharmaceutical Use of Salix - Förster, Nadja; Antoniadou, Kyriaki; Zander, Matthias; Baur, Sebastian; Mittermeier-Kleßinger, Verena Karolin; Dawid, Corinna; Ulrichs, Christian; Mewis, Inga (Frontiers in Plant Science, 2021)
Willow bark is traditionally used for pharmaceutical purposes. Evaluation is so far based on the salicylate content, however, health promoting effects of extracts might be attributed to the interaction of those salicylates with other compounds, which support and complement their action. So far, only S. purpurea, S. daphnoides, and S. fragilis are included in pharmaceutical extracts. Crossing with other species could result in a more diverse secondary metabolite profile with higher pharmacological value. With the help of targeted inter- and intraspecific crossing, new chemotypes were generated, whereby nine different Salix genotypes (S. alba, S. daphnoides, S. humboldtiana, S. lasiandra, S. nigra, S. pentandra, S. purpurea, S. x rubens, S. viminalis) were included in the study. Based on substances known for their health promoting potential and characteristic for Salix (selected phenolic compounds including salicylates), a targeted metabolomics analysis and clustering of 92 generated Salix clones was performed revealing four different cluster/chemoprofiles. In more specific, one group is formed by S. daphnoides clones and inter- and intraspecific hybrids, a second group by S. viminalis clones and inter- and intraspecific hybrids, a third group generally formed by S. alba, S. pentandra, S. x rubens, and S. lasiandra clones and hybrids, and a fourth group by S. purpurea clones and inter- and intraspecific hybrids. Clustering on the basis of the selected phenolic compounds can be used for identifying Salix clones with a different compound profile. New combinations of secondary plant metabolites offer the chance to identify Salix crosses with improved effects on human health.